DETERMINATION OF ACCOUNTING MANIPULATIONS IN THE FINANCIAL STATEMENTS USING ACCRUAL BASED INVESTMENT RATIOS - Dragan Gabrić (Economic Review)
The subject of this paper is research of an impact of accrual based investment ratios on the determination of accounting manipulations in the financial statements of the listed companies in the Federation of Bosnia and Herzegovina (FBiH). The main objective of this research is to identify the accrual based investment ratios that contribute to the determination of accounting manipulations and to create a model of an impact of accrual based investment ratios on determination of accounting manipulations in financial statements of the companies. Methodological approach to research determination of accounting manipulations is based on accrual based financial ratios - the investment indicators. Researchers have used the technique of analysing the content of auditing and financial statements to collect research data for the period from 2010 to 2014 on a sample of the listed companies from the capital market in FBiH. In the researc h, inferential statistics has been applied as a fundamental form of the scientific-cognitive process. The obtained results have been presented by graphs and tabular views. The research results revealed that the accrual based investment ratios contribute to the determination of accounting manipulations in the financial statements of the listed companies in FBiH. Furthermore, a model of impact has been obtained, which indicates that accrual based investment ratio Earnings Per Share (EPS) has a significant impact on the determination of the accounting manipulations in the financial statements. Finally, the research revealed that accrual based investment ratios are a useful tool in determining the accounting manipulations in the financial statements of the companies.